Review on properties, physics, and fabrication of two-dimensional material-based metal-matrix composites (2DMMCs) for heat transfer systems - Lupoi, Rocco (My University, 2025)
In the exploration of new materials development, 2D materials have received much attention due to their outstanding properties in terms of e.g. strength, and electrical and thermal conductivities. Graphene and boron nitride, amongst other 2D materials, are renowned for their exceptional thermal conductivity. In this review, we examine the properties, physics, and fabrication techniques of 2D material-based metal-matrix composites (2DMMCs) with a specific focus on heat transfer systems. The on-going demand for better electronic cooling systems in combination with advancements in mass production techniques of 2D materials facilitates the application of 2DMMCs in heat transfer systems. However, currently, the thermal behaviour of 2DMMCs remains largely uncategorized, strengthening the timely context of this review. Next to recent research progress, material properties, production techniques and strategies for improving thermal conductivity of 2DMMCs are addressed in this work. Methods to reliably assess the thermal conductivity of 2D enhanced materials are discussed alongside the fabrication techniques for 2D-material feedstocks for 2DMMCs production. Also, current limitations in the heat transfer capabilities of 2DMMCs, alongside prospects for enhancing thermal properties through emerging technologies, such as additive manufacturing, are addressed.
PUBLISHED